1984
DOI: 10.1161/01.hyp.6.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of nutritional factors in the incidence of cerebral lesions in stroke-prone spontaneously hypertensive rats.

Abstract: SUMMARYThe incidence of cerebral lesions in stroke-prone spontaneously hypertensive rats appears to depend on the severity of the hypertension and nutritional factors. Comparison of American and Japanese commercial rat diets revealed a much higher incidence of stroke in rats receiving the Japanese diet (88% vs 30% by 9 months of age). Analyses of the diets indicate that perhaps the most important difference in the two diets is the protein content. Based on complete amino acid analyses of the protein in these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 7 publications
0
44
0
Order By: Relevance
“…It is well known that dietary nutrients such as sodium, potassium, calcium, and magnesium influence blood pressure (3)(4)(5)(6). Moreover, several investigators have suggested that dietary protein and amino acids could also influence blood pressure and thus affect the development of hypertension (7,8). Recently, emphasis has been focused on the relationship between taurine, a sulfur amino acid, and cardiovascular disease (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that dietary nutrients such as sodium, potassium, calcium, and magnesium influence blood pressure (3)(4)(5)(6). Moreover, several investigators have suggested that dietary protein and amino acids could also influence blood pressure and thus affect the development of hypertension (7,8). Recently, emphasis has been focused on the relationship between taurine, a sulfur amino acid, and cardiovascular disease (9).…”
Section: Introductionmentioning
confidence: 99%
“…First, an increase in protein intake may increase plasma amino acids that may directly influence proximal sodium reabsorption or alter cell permeability and subsequently increase renal plasma flow, renal size and glomerular filtration rate. [24][25][26][27] Second, the amino acid arginine may act as a vasodilator through nitric oxide and contribute to BP lowering. 28 Plant foods including soy products, nuts, seeds and certain whole grains like oats are all good sources of arginine but so are animal foods such as animal meats, seafood, dairy products and eggs.…”
mentioning
confidence: 99%
“…13 As the most important difference in the 2 diets was the protein content, it has been proposed that the increased protein proportion present in the American rat diet could prevent stroke in SHRSP, although fat and carbohydrate proportions that also differ were not considered. 13 In humans, in the Nurses' Health Study, animal protein intake or saturated fatty acid intake was inversely associated with intraparenchymal hemorrhage, and the excess risk associated with low saturated fat intake was observed primarily among women with a history of hypertension. 1 In the same cohort, high carbohydrate intake was associated with an elevated risk of hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%